Customer relationship management and innovative strategies in tourism industry - DR. GIGI G S; MS. DIVYA A (The journal of contemporary issues in business and government, 2020)
Customer relationship management (CRM) is a mixture of individual, process and technology that tries to understand their company’s customers. Most of the tourism companies coordinated ways to deal with overseeing connections by focusing on customer maintenance and relationship improvement. CRM has developed from progresses in technology and hierarchical changes in customer driven processes. Tourism companies that effectively execute, customer relationship management will receive the benefits in customer loyalty and long run productivity or profitability. In any case, effective execution is most of the tourism company requires customer relationship management all inclusive, cross functional, customer focused business measure re- designing the framework. In spite of the facts CRM is a technology, customer relationship management is an only technology which helps the tourism industry in bringing solutions for the customers in order to satisfy their needs and wants. Dealing with an effective CRM execution requires a coordinated and adjusted way to deal with technology, process and individuals. The sample size of the study is 70 and tools which are used to find secondary data are frequency analysis, mean analysis, independent t test, ANOVA (one way), and regression analysis.